2016
DOI: 10.1111/ijn.12438
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors, cross‐cultural stressors and postpartum depression among immigrant Chinese women in Japan

Abstract: The purpose of this mixed-method design study was to examine factors contributing to depression among immigrant Chinese women (primipara and multipara) (n = 22) delivering a child for the first time in Japan. Data were obtained just after hospital discharge by using the Edinburgh Postnatal Depression Scale (EPDS), the Social Support Scale, a new scale to measure crosscultural stressors in the postpartum setting and a visual analogue scale for stress and a demographic survey. The average EPDS score was 9.0 (SD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
34
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 16 publications
4
34
1
Order By: Relevance
“…The present figure was higher than the prevalence of PPD reported in other studies carried out in China using the EPDS scale. [9][10][11] Similar to the present results, a Japanese study of new mothers 12 found that depressive symptoms were evident in 55% of immigrant peer-reviewed journals between 1998 and 2008 13 showed that the prevalence of PPD in Asian countries displayed a wide range from 4% to 63%. The distinguishing feature of the present study in comparison with other studies that have examined the prevalence of PPD lies in the fact the present study involved investigation of the long-term effects of sibling deprivation on psychological adjustment.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The present figure was higher than the prevalence of PPD reported in other studies carried out in China using the EPDS scale. [9][10][11] Similar to the present results, a Japanese study of new mothers 12 found that depressive symptoms were evident in 55% of immigrant peer-reviewed journals between 1998 and 2008 13 showed that the prevalence of PPD in Asian countries displayed a wide range from 4% to 63%. The distinguishing feature of the present study in comparison with other studies that have examined the prevalence of PPD lies in the fact the present study involved investigation of the long-term effects of sibling deprivation on psychological adjustment.…”
Section: Discussionsupporting
confidence: 88%
“…The present figure was higher than the prevalence of PPD reported in other studies carried out in China using the EPDS scale . Similar to the present results, a Japanese study of new mothers found that depressive symptoms were evident in 55% of immigrant Chinese women. A systematic review of articles published in English peer‐reviewed journals between 1998 and 2008 showed that the prevalence of PPD in Asian countries displayed a wide range from 4% to 63%.…”
Section: Discussionsupporting
confidence: 85%
“…The prevalence rate of PPD was as high as 34.0%. Likewise, a Japanese study of new mothers found that 54.5% of migrant Chinese women had elevated levels of postpartum depressive symptoms as indicated by scores on EPDS [6]. Several other Canadian studies similarly found that the risks for PPD in immigrant Chinese women were significantly higher than that of native-born women [2][3][4].…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review found that immigrant women are twice as likely to experience PPD as nonimmigrant women [5]. In a cross-sectional study conducted in Tokyo, Japan, migrant Chinese women had elevated depression symptoms postnatally than Japanese-born women [6]. Several studies conducted in Ontario, Canada have found migrant Chinese women had increased risk of PPD compared to their Canadian-born counterparts [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…52 On the other hand, low socioeconomic status is a risk factor for PPD. 53 Therefore, it is likely that mothers who have an emergency CS have a lower socioeconomic status than those who undergo selective surgery and are more prone to PPD. This relationship was also confirmed in a study conducted in the Netherlands in which the odds ratio of PPD was higher mothers with CS (OR = 1.53).…”
Section: Discussionmentioning
confidence: 99%